(untitled) (Global Journal of Human-Social Science, 2012)
Religious fundamentalism,following 9/11 attack in the United States, has a assumed new a dimension in Nigeria. The current wave of religious fundamentalism raises the concern whether Nigeria is a normless society or the problem of normlesness has been inherent in cultures and traditions of the Nigeria inhabitants before the arrival of Islam and Christianity. This paper argues that religion in the pre-colonial times was developed with the need to provide a world view for the people to understand themselves, and to direct collective consciousness toward achieving societal goals. The paper contends that the current wave of religious fundamentalism became fossilized through religious manipulation and politicization in the post colonial era. The paper concludes that unless our universal cultural norms and value are resorted to redirect behavioural attitude toward governance in Nigeria, religious fundamentalism would thrive on.